UJI BERBAGAI ALAT DETEKSI BIRAHI TERHADAP ANGKA KEBUNTINGAN PADA SAPI PERAH DI KOPERASI TUNAS SETIA BARU KABUPATEN PASURUAN - Andriyanti, Silvia Rani; Hariadi, Mas'ud; Darsono, Roesno; Srianto, Pudji; wurlina, wurlina; Restiadi, Tjuk Imam (Universitas Airlangga, 2018)
This research aims to determine the use of various estrus detection devices before artificial insemination as measured by pregnancy rate. The researcher used a sample of 60 cows were used in this research which is divided into four groups as a control and treatment groups (Thermopin®, Hauptner and Draminski groups), and each cow was detected for the sign of estrus by three devices that were Thermopin®, Hauptner and Draminski prion when doing an artificial insemination. The cows were observed to 45 days after artificial insemination for observing pregnancy. This research method is the exploration scope to prove the effect of various estrus detection tool against pregnancy rates. The result of ANOVA test, there is the effect of using a various estrus detection devices against pregnancy rates. Samples tested by Draminski with average (1.53±0.51) resulted in a 53,3% pregnancy rate, the samples were tested with Hauptner with average (1.67±0,48) resulted in pregnancy rate 66,7%. Without treatment or control, sample with an average of (1.67±0,48) resulted in a 73,3% pregnancy rate. While samples were tested with Thermopin® with average (2.00±0,00) resulted in a 100% pregnancy rate. In conclusion, Thermopin® the best detection tool than other estrus detection devices.